Oral Lesions: The Clue to Diagnosis of Pemphigus Vulgaris - Diana Kuriachan; Rakesh Suresh; Mahija Janardhanan; Vindhya Savithri (Hindawi Limited, 2015)
Pemphigus is a group of potentially fatal dermatoses with both cutaneous and oral manifestations. Characterized by the appearance of vesicle or bullae, their manifestations in the oral cavity often precede those on the skin by many months or may remain as the only symptoms of the disease. It is therefore important that the oral manifestations of the disease are recognized on time, to make a proper diagnosis and initiate timely treatment. Here we present a case of Pemphigus Vulgaris (PV) that presented with oral lesions at multiple sites including tongue, to highlight the importance of timely recognition of the oral lesions during routine dental practice for the diagnosis and management of this disease.